Controle de Colletotrichum lindemuthianum (Sacc. Et Mag.) Scrib na cultura do feijão (Phaseolus vulgaris L.) pelo extrato de cogumelo Pycnoporus sanguineus (L. ex Fr.) - Assi, Lindomar (2005)
The concern with the environment and the human health has stimulated the search for methods that reduce the use of fungicides in the control of phytopathogens. Considering many positive results already reached by using induced resistance, and the great demand for new elicitors of resistance to pathogens, this work had the objective to evaluate the fungitoxic effect in vitro of the aqueous extract (EA) of Pycnoporus sanguineus basidiocarp, against Colletotrichum lindemuthianum and evaluate under greenhouse conditions, the control of anthracnose in beans, as well as the induction of resistance by the determination of peroxidases activity. For the assays in vitro were used EAs, in the concentrations of 1, 5, 10, 15 and 20 %, autoiclavated or not. And evaluating the micelial growth and spores germination of C. lindemuthianum. For the in vivo assays, EAs not autoclavated at 5, 10 and 20% were sprayed in 7th´s leaves of beans plants three days before the inoculation of the pathogen (5x104 conidia/mL) that was occurred in 7th´s and 8th´s leaves. Water and fungicide (azoxystrobin 0,6 g. p. c./L) were used as control tratments. For peroxidase, 7th´s and 8th´s leaves were sampled at the moment of treatments and after three, six, nine and twelve days. The results showed direct antimicrobial activity of the EAs of P. sanguineus, with inhibition of up to 96% of the germination in vitro of the spores of C. lindemuthianum, independent of the autoclavation of the extracts. The EAs stimulated in up to 34 % the micelial growth. In the plants, eA 20% controlled the anthracnose with reduction of 70% severity in 7th´s leaf (treated and inoculated), while for the fungicide the reduction was of 73%. For 8 th´s leaf (only inoculated), the EAs at 5, 10 and 20% reduced the severity in 58, 64 and 68%, respectively, while for the fungicide the reduction was of 74%. This reduction in severity can be associated with the activity of peroxidase, which was presented high, in both 7th´s and 8th´s leaves in the moment of the inoculation, it means, three days after the treatment. These results indicate the P. sanguineus extracts potential for control of anthracnose in beans plants, that can occurr by direct antimicrobial activity and/or local and systemic induction.